Effect of combinations of rumen-protected methionine plus rumen-protected lysine on performance of finishing steers - Goldy, G.; Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feed efficiency for finishing steers was significantly improved (7.4%) when rumen-protected methionine and lysine were added to a finishing ration.
Keywords: Beef; Methionine; Lysine; Rumen; Finishing steers